Causes and Solutions of â€œTragedy of the Commonsâ€ in Natural Resources Management of Muncar Coastal Areas - Wulandari, Dwi; Yunika Puspasari, Emma; Anita Yunikawati, Nur; Soseco, Thomas; Shandy Narmaditya, Bagus; Istiqomah, Niâ€™matul; Hardinto, Prih; Hadi Utomo, Sugeng; Witjaksono, Mit (International Journal of Engineering and Technology, 2018)
The tragedy of commons exists where natural common resources are overused. Every user is encouraged to maximize their utilization by taking as much as they can, left environmentâ€™s ability to regenerates behind. As a result, there will be a decreasing result. The condition exists in Muncar in Banyuwangi, Indonesia. This coastal area has to accommodate an increasing number of fishing fleets with more advanced technology, which creates a diminishing volume in fishing catches. This research explores the tragedy of commons in Muncar, Indonesia. We use the qualitative approach with the phenomenological interpretative paradigm. We interviewed stakeholders as well as fishermen in Muncar. The result of this study (1). The increasing number of fishing fleets are accompanied with more advanced technology. This allows fishermen to catch fish in higher volume. Also, there is a negligence in environment-friendly concern because of economic reason. (2). The tragedy of commons is caused by unclear regulation about fish regulation along the Muncar Coastal Area. The development of infrastructure in Muncar is not well equipped with adequate utilities such as disposal waste facilities. Also, the development of industrial zones in Muncar is not well planned.Â Â